â€œCAKIL JUGA MANUSIAâ€ (DASAR KONSEPTUAL ME-MANUSIA-KAN CAKIL DALAM PERTUNJUKAN) - Wibowo, Anggono Kusumo (Institut Seni Indoensia Surakarta, 2016)
Preparation of dance with the title â€œCakil Juga Manusia (Cakil Also Human: Ing)â€ inspired by someÂ contemporary thinking associated with the figure of Cakil. In the world of show tradition PuppetÂ Stage, Cakil identical as antagonist iconic to the nature of evil and bad. Nevertheless, its presence isÂ always awaited by the audience because of its motion is interesting, distinctive, attractive and acrobatic. In addition to the motion, the character traits that ngglece using everyday language of populistÂ dialogue considered communicative audience. The show is entertaining and communicative as well asÂ the populist spur compilers for presenting a claim jogetan Cakil new ones with shades of populist. Ina fragment of a story, Cakil presented as being humane because it has love, has the property ofÂ honest, innocent, and innocent. The work â€œCakil Juga Manusiaâ€ try to work on one scene that isÂ packaged in a dance drama story about inner feelings Cakil figure in romance. The process of thisÂ work is done by a coherent process stages. Starting from the literature, field studies, data reduction,the discovery of forms till, independent search process, the selection of dancers, the production teamÂ selection, implementation of the exercises, the deepening and strengthening of the work, up to theÂ staging. This work is specifically aimed to re-discover the contrast of the characters Cakil. The rationale behind the idea of this work is the desire to realize the humanity of Cakil, that he has a love,feelings, loyalty, and a sense of sensibility. This effort will greatly affect the appearance of vokabulervokabuler new motion in the frame of a typical motion Ceklekan. Novelty characters and their CakilÂ vokabuler new motion will be attempted to be developed in the frame of narrative fragments of stories. This will add to the challenges of exploration and character motion in the cultivation processÂ works.Keywords: Cakil, the concept works, fragments of Love, and Ceklekan.